2005
DOI: 10.1152/ajpcell.00411.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Na+/Ca2+ exchange in regulating cytosolic Ca2+ in cultured human pulmonary artery smooth muscle cells

Abstract: A rise in cytosolic Ca2+ concentration ([Ca2+]cyt) in pulmonary artery smooth muscle cells (PASMC) is an important stimulus for cell contraction, migration, and proliferation. Depletion of intracellular Ca2+ stores opens store-operated Ca2+ channels (SOC) and causes Ca2+ entry. Transient receptor potential (TRP) cation channels that are permeable to Na+ and Ca2+ are believed to form functional SOC. Because sarcolemmal Na+/Ca2+ exchanger has also been implicated in regulating [Ca2+]cyt, this study was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
97
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 66 publications
4
97
0
Order By: Relevance
“…Conversely, an enhanced local rise in [Na + ] cyt due to enhanced I Na activity, could have a similar effect on both NCX activity and [Ca 2+ ] cyt . In a recent study, we demonstrated that human PASMC express high levels of NCX-encoding proteins, NCX1 and NCKX3 [37]. Enhanced reverse-mode NCX activity produced not only an increase in [Ca 2+ ] cyt , but also promoted PASMC proliferation [37].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, an enhanced local rise in [Na + ] cyt due to enhanced I Na activity, could have a similar effect on both NCX activity and [Ca 2+ ] cyt . In a recent study, we demonstrated that human PASMC express high levels of NCX-encoding proteins, NCX1 and NCKX3 [37]. Enhanced reverse-mode NCX activity produced not only an increase in [Ca 2+ ] cyt , but also promoted PASMC proliferation [37].…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, we demonstrated that human PASMC express high levels of NCX-encoding proteins, NCX1 and NCKX3 [37]. Enhanced reverse-mode NCX activity produced not only an increase in [Ca 2+ ] cyt , but also promoted PASMC proliferation [37]. Preliminary experiments conducted within our lab suggest that TTX-sensitive Na + channel activation does not influence the histamine-induced release of Ca 2+ from the SR in cultured human PASMC (Mauban and Yuan, unpublished observations), or serum-induced PASMC proliferation (Remillard and Yuan, unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…However, that may not be the mechanism by which HGMs generate oscillation, since CB-DMB does inhibit nor mitochondrial nor ER Ca 2ϩ channels/transporters in applied concentration (37), and no oscillations could be observed after applying it. In pulmonary artery smooth muscle cells, NCX plays an important role in regulating cytosolic Ca 2ϩ levels; however, in these cells Ca 2ϩ increases via the NCX and store-operated entry (43). Although NCX regulates the cytosolic Ca 2ϩ in the HGMs in a similar way, store-operated entry does not play a role in HGMs, since inhibiting the NCX results in Ca 2ϩ depletion, not store depletion-mediated Ca 2ϩ entry.…”
Section: G560mentioning
confidence: 99%
“…Furthermore, without proper Ca 2ϩ signaling, resting cells cannot get over the G 0 phase (1). In pulmonary artery smooth muscle cells, Ca 2ϩ enters the cytosol after store depletion via the reverse mode of NCX, and the NCX inhibitor KB-R7943 inhibited cell proliferation via disorganization of intracellular Ca 2ϩ signaling (43).…”
Section: G560mentioning
confidence: 99%
See 1 more Smart Citation